Juvenile xanthogranuloma: clinical-pathological approach. Case reports: Xantogranuloma juvenil: enfoque clínico-patológico. Reporte de dos casos - Palomino Portilla, Eugenio A. (2022)
Juvenile Xanthogranuloma is a non-neoplastic skin lesion of the non-Langerhans histiocytosis type, which mainly affects the pediatric population and usually has a self-limited course. Exceptionally, the lesion is multifocal, ocular and even visceral, causing severe complications. We present the case of two 10-year-old female patients, with no other symptoms or important history, both with a single lesion, one on the thigh, with 3 months of evolution, the other on the scalp, with 4 months of evolution, both with progressive growth and surgically removed. The anatomopathological study identified multiple histiocytes in the dermis, with cytoplasmic lipidization and forming giant multinucleated cells, some of the Touton type, characteristic of this lesion. This unusual entity is reviewed, with emphasis on the histopathological criteria and the usual clinical course.